Diseño de un sistema de costos por ordenes de producción para la asociación de productores agropecuarios patain perteneciente al Cantón Salcedo - Macas Conde, Cynthia Maribel (2019)
Technological progress and national and international competition in the market have made companies, associations or organizations seek to be updated within their administration, so it is important to have a cost system to improve decision making. For which it is important that the Association of Agricultural Producers Patain, dedicated to the production of pulps and jams, have a Cost System for Production Orders for the benefit of both their customers and each of the partners. It was established that the main problem facing the Association is that they perform the calculation of their costs in an empirical way since they do not take into account the operating costs involved in the manufacture of the product, so this project aims to The design of a cost system for production orders through the identification of the different productive processes carried out in the Association, which allows the efficient use of the resources used, is essential. For the development of the project, methods have been used such as the investigation and bibliographic compilation, documentation of the association, techniques such as observation, and instruments such as the interview and the observation sheet addressed to the production area in order to obtain all the information necessary for the achievement of the project. The following results have been reached: the productive process is not continuous, it is very scarce due to the high cost of selling to the public of each of its products, in addition to the costs that are calculated, they do so empirically trying to generate a greater utility and not taking into account the real cost of the product that is made. It was determined that the design of a cost system will allow a better management, a chronological order with respect to each of the processes that are used for the elaboration of each product in order to obtain a more real cost, a greater facility to calculate the total values of each element of the costs in this case Raw Material, Labor, Indirect Manufacturing Costs (CIF) and that you can make sound decisions that benefit your customers and each of the partners.